UPAYA MENINGKATKAN HASIL BELAJAR SEJARAH MELALUI PEMANFAATAN ZOOM MEETING MASA PANDEMI COVID -19 - NURTANTI NURTANTI (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2022)
The goal to be achieved in this research is to find out how to use the zoom meeting for the learning process during the Covid-19 Pandemic in history lessons in class XII IPS 1 SMAN 1 Caringin in the 2021/2022 school year. The data sources of this research were 3 students of class XII IPS 1 SMAN 1 Caringin. The time of this research is carried out in the Odd Semester of the 2021/2022 Academic Year for 4 months. The data collected is quantitative and qualitative data. Quantitative data is data obtained from formative test results in each cycle. While qualitative data in the form of observations in each learning cycle. The results of the study using the zoom meeting for the learning process during the Covid-19 Pandemic to improve learning outcomes for class XII IPS 1 SMAN 1 Caringin in the History result lesson in the initial observation (pre-cycle) obtained only 11 students or 33.33% of all students. In the first cycle there were a number of students who succeeded in improving learning outcomes, increasing by 4 to 15 students or 45.45%. In cycle II, students who succeeded in increasing their learning outcomes reached 27 or 81.82% of 33 students. The success of students in the lesson of History results in class XII IPS 1 SMAN 1 Caringin experienced a significant increase. Student learning outcomes in the pre-cycle with a class average of 57.98, then in the first cycle increased to 69.49 but this has not reached the expected KKM which is 71, in the second cycle it increases to 82.63 and has exceeded the KKM which determined. The conclusion that can be drawn is that the use of the zoom meeting has succeeded in increasing the learning outcomes of History so that it is suitable for SMAN 1 Caringin. ABSTRAKTujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui bagaimana pemanfaat zoom meeting untuk proses pembelajaran pada masa Pandemic Covid-19 pada pelajaran sejarah di kelas XII IPS 1 SMAN 1 Caringin tahun pelajaran 2021/2022. Sumber data penelitian ini adalah siswa kelas XII IPS 1 SMAN 1 Caringin sejumlah 3 siswa. Waktu Peneltian ini dilaksanakan pada Semester Ganjil Tahun Ajaran 2021/2022 selama 4 Bulan. Data yang dikumpulkan adalah data kuantitatif dan kualitatif. Data kuantitatif adalah data yang diperoleh dari hasil tes formatif pada setiap siklus. Sedangkan data kualitatif berupa hasil observasi pada tiap siklus pembelajaran. Hasil penelitian pemanfaat zoom meeting untuk proses pembelajaran pada masa Pandemic Covid-19 untuk meningkatkan hasil belajar kelas XII IPS 1 SMAN 1 Caringin pada pelajaran hasil Sejarah pada observasi awal (prasiklus) didapatkan hanya 11 siswa atau 33,33% dari seluruh siswa. Pada siklus I ada sejumlah siswa yang berhasil meningkatkan hasil belajar bertambah 4 menjadi siswa 15 atau 45,45%. Pada siklus II siswa yang berhasil meningkat hasil belajarnya mencapai menjadi 27 atau 81,82% dari 33 siswa. Keberhasilan siswa dalam pelajaran hasil Sejarah pada kelas XII IPS 1 SMAN 1 Caringin mengalami adanya peningkatan yang signifikan. Hasil belajar siswa pada pra siklus dengan rata-rata kelas 57,98, kemudian pada siklus 1 meningkat menjadi 69,49 namun hal ini belum mencapai KKM yang diharapkan yaitu ?71, pada siklus II meningkat menjadi 82,63 dan telah melebihi dari KKM yang ditentukan. Kesimpulan yang dapat diambil bahwa pemanfaatan zoom meeting telah berhasil meningkatkan hasil belajar Sejarah sehingga layak untuk di SMAN 1 Caringin.